Characterization of the atypical antipsychotic drug aripiprazole cytotoxicity in the neutrophil model cell line HL-60 - Courtney A. Swain; Emily J. Robbs; Lindsay Verma; Heaven Brandt; Alexandra L. Seppaenen; Peter J. Cavnar (PLoS ONE, 2025)
Atypical antipsychotics are widely used for the treatment of mental and behavioral disorders such as bipolar disorder, obsessive-compulsive disorder, and schizophrenia. However, these drugs can occasionally induce neutropenia or agranulocytosis, characterized by a significant reduction in circulating neutrophils, the primary white blood cells responsible for immune responses. This drug-induced neutropenia poses a considerable risk of life-threatening infections. However, the precise mechanism by which atypical antipsychotics induce neutropenia remains unclear. This study investigates the effects of four atypical antipsychotics, namely – aripiprazole, clozapine, olanzapine, and quetiapine – on the human neutrophil model cell line HL-60. These drugs, which modulate dopamine receptor signaling alongside other mechanisms, were analyzed for their effects. Among these, aripiprazole – but not the others – uniquely induced apoptosis in a dose-dependent manner, accompanied by an increased expression of pro-apoptotic genes – BAK, BCL10, and caspase-3. Moreover, our study elucidates that while differentiated HL-60 cells express D1-like and D2-like dopamine receptors, aripiprazole’s cytotoxic effects appear to operate through dopamine-independent pathways and significantly reduce phosphorylated Src family kinase levels. Our results align with previous studies suggesting that aripiprazole exhibits cytotoxic properties in neutrophils. Nevertheless, further investigations are warranted to investigate the mechanisms underlying aripiprazole-induced apoptosis in neutrophils.